Research handbook of women's entrepreneurship and value creation - Yousafzai, Shumaila; Henry, Colette; Boddington, Monique; Sheikh, Shandana; Fayolle, Alain (Research handbooks in business and management series, 2022)
"This Research Handbook highlights the importance of women as agents of change, acknowledging women entrepreneurs' efforts and supporting their value-creation activities. With important implications for policymaking, contributing authors direct attention to and provide evidence for the positive contribution of women entrepreneurs to the economy, regardless of their businesses' size and formal status. Challenging the underperformance hypothesis associated with women entrepreneurs, chapters present evidence that women do not underperform in their businesses, but that they add value even in constrained environments. This intends to shift the focus of research from questions like 'what do entrepreneurs do?' to 'how do they do it?', focusing on the unique ways in which each women entrepreneur creates value, and 'for whom do they do it?', looking at the multiple value outcomes women entrepreneurs create and the beneficiaries of that value. With a global perspective on women's entrepreneurship and their value creation, this Research Handbook will be vital reading for researchers of entrepreneurship, as well as government agencies and policymakers interested in promoting entrepreneurial activity"--